A Case of Primary Non-Hodgkin's Lymphoma of the External Auditory Canal. (4th August 2013) - Bruschini, Luca; De Vito, Andrea; Fortunato, Susanna; Pelosini, Marco; Cervetti, Giulia; Petrini, Mario; Berrettini, Stefano
Abstract : Lymphomas represent the second most frequent malignant tumor (incidence 2.5%) in the head and neck region. Non-Hodgkin lymphomas (NHLs) present with cervical lymph node involvement, but in 40% extranodal site could be primary involved: nasopharynx, the lacrimal sac, the temporal bone, or the others areas. NHLs of the ear are rarely reported. In this report, we described a patient with primary NHL of the external ear canal who was successfully treated with surgical excision and chemotherapy.